Efficacy of massage and stretching for controlling hamstring muscle spasticity in children with diplegic spastic cerebral palsy: A comparative study - Almalty, Abdulmajeed R; Hussein Mashaal, Ahmed; Hawamdeh, Mohannad; Bleedy, Nermeen; Abdelnour, Hassan M; Mahmood, Safi (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Background: Massage therapy is utilized to alleviate muscle spasticity in children with cerebral palsy, typically lasting at least 15 min per muscle group, which may result in lower family compliance with the home program. Objective: This study aimed to explore the impact of stretching alone or in combination with short-term massage on reducing hamstring muscle spasticity and enhancing knee range of motion (ROM) in children with diplegic spastic cerebral palsy. Methods: Twelve children diagnosed with diplegic spastic cerebral palsy (6–12 years old) were randomly divided into two groups: the first received massage and stretching exercises, and the second received stretching exercises only on the hamstring muscle. The Modified Ashworth Scale was used to measure the stiffness of the hamstring muscle, and the ROM of knee flexion was measured using a manual goniometer. ROM and modified Ashworth scale (MAS) were measured at baseline and after 1 and 2 weeks of treatment, respectively. Both legs of each participant received treatment for 2 weeks, with the duration of massage being 5 min and the duration of stretching being 30s with three repetitions. Results: Both methods reduced hamstring spasticity after two weeks; however, ROM improved after the first week and more significantly after the 2nd week. Conclusion: Stretching exercises, whether performed alone or in combination with short-term massage, have been found to be equally effective for treating spastic muscles. Although there was an improvement in spasticity after the first week of short-term massage, the difference was not statistically significant.